Development of creative competence of future engineers in the process of their vocational training - Kuleshova, V. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the problems that are urgent for engineering education. Peculiarities of formation of creative competence of future engineers are revealed. The competence of an engineer is considered to be a more professional characteristic. The author convincingly proves that creative competence should be the necessary component of professional competence of the future engineer, developed in the process of gaining experience of what has been accumulated, which leads then to the change and transformation of the existing experience. V. Kuleshova states that there is an apparent lack of systematicness in the practice of teaching "inventiveness", which is the basis of creative competence. Consequently, in comparison with more technically advanced countries, this lack of systematicness results in a smaller number of registered inventions, technological innovation lag, import dependence and, most importantly, in a sharp decline in the prestige of engineering work. Therefore, the net result of engineering education should be a welldeveloped creative mentality and creative way of professional thinking aimed at finding brandnew solutions to technical problems. The article reveals the essence of the development of creative competence of future engineers in the process of their vocational training